Laccase and other ligninolytic enzyme activities of selected strains of Trametes spp. from different localities and substrates - Tomsovský, M; Homolka, L (Folia microbiologica, 2003)
Eighty-three strains belonging to three species of the genus Trametes FR. (T. versicolor, T. hirsuta and T. ochracea) collected in different localities and on different substrates were screened for laccase production. The production of other lignin-modifying enzymes--manganese peroxidase (MnP) and lignin peroxidase (LiP)--and the decolorization ability were also determined in 21 of them. Production variability was relatively high and no significant correlation was found between the origin of the strains (locality, substrate) and the enzyme production. Dikaryons of all 3 species (but not of all their strains) exhibited LiP activity, which was not detected in the respective monokaryons.
Keywords: lignin; metoda Monte Carlo; Multivariate Analysis; Peroxidases; Yugoslavia; Monte Carlo Method; oxidoreduktasy; Lignin; Bulgaria; lakasa; multivariační analýza; Altitude; Czech Republic; Laccase; Bulharsko; peroxidasy; Česká republika; Jugoslávie; Basidiomycota; Oxidoreductases; nadmořská výška